Religious elements of media reporting on migrants - a comparison of journalist and reader perspectives - Stamenković, Ivana (Sociološki pregled, 2024)
Given that media narratives about migrants are permeated with political, economic, and religious factors, the aim of this analysis is to identify and compare patterns in reporting on the migrant crisis with patterns in readers’ comments. This is to determine whether there are differences between these narratives in terms of how migrants are described and referred to, with a particular focus on the presence of religious elements. The sample used to analyze media reporting patterns in relation to the migrant crisis consists of journalistic articles from the online editions of the daily newspapers Politika and Kurir. Additionally, the sample includes the readers’ comments accompanying these articles about the migrant crisis and migrants, which were published during 2015 and 2017. The research has found that there is a statistically significant difference between the reporting patterns of journalists and the commenting patterns of readers concerning several reference dimensions (Stamenković, 2021). Among these, the category of Otherness, with emphasized religious elements, stands out particularly, as well as the negative characterization of migrants as an aggressive, militant, and conquering group.
Keywords: media; migrants; religious elements; Islam; fear